2020
DOI: 10.1074/jbc.ra120.014259
|View full text |Cite
|
Sign up to set email alerts
|

Extended subsite profiling of the pyroptosis effector protein gasdermin D reveals a region recognized by inflammatory caspase-11

Abstract: Pyroptosis is the caspase-dependent inflammatory cell death mechanism that underpins the innate immune response against pathogens and is dysregulated in inflammatory disorders. Pyroptosis occurs via two pathways: the canonical pathway signaled by caspase-1 and the noncanonical pathway regulated by mouse caspase-11 and human caspases-4/5. All inflammatory caspases activate the pyroptosis effector protein gasdermin D, but caspase-1 mostly activates the inflammatory cytokine precursors pro-interleukin-18 and pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 58 publications
5
33
0
Order By: Relevance
“…When activated, reminiscent of caspase-1, the noncanonical inflammasome caspases convert GSDMD into GSDMD-N to induce pyroptosis. In contrast to caspase-1, caspase-11 is not able to process pro-IL-1b and pro-IL-18, while caspase-4 may process pro-IL-18 but not pro-IL-1b, and caspase-5 possesses a weak ability to process pro-IL-1b and pro-IL-18 (24,77,78). These results suggest that noncanonical inflammasomes play a more important role in the induction of pyroptosis than in the direct maturation of IL-1b and IL-18.…”
Section: Structure and Activation Of Inflammasomesmentioning
confidence: 99%
“…When activated, reminiscent of caspase-1, the noncanonical inflammasome caspases convert GSDMD into GSDMD-N to induce pyroptosis. In contrast to caspase-1, caspase-11 is not able to process pro-IL-1b and pro-IL-18, while caspase-4 may process pro-IL-18 but not pro-IL-1b, and caspase-5 possesses a weak ability to process pro-IL-1b and pro-IL-18 (24,77,78). These results suggest that noncanonical inflammasomes play a more important role in the induction of pyroptosis than in the direct maturation of IL-1b and IL-18.…”
Section: Structure and Activation Of Inflammasomesmentioning
confidence: 99%
“…This is in line with reports showing that caspase-1 activation in Gsdmd -deficient mouse macrophages engages rapid apoptosis via Bid cleavage 1416 . Of note, while mouse caspase-11 is apparently not able to induce this type of apoptosis 79 , we found that optoCaspase-4 and −5 caused GSDMD-independent apoptosis, which could possibly be due to their wider substrate profile 17 . OptoCaspase activation efficiently induced pyroptosis in commonly used laboratory cell lines, such as MCF7 cells, HeLa, Caco-2, HT-29 and HaCaT, ( Fig.…”
Section: Resultsmentioning
confidence: 58%
“…as their catalytic domain is most similar to that found in hCasp-4, a caspase that has no considerable ICE activity (Bibo-Verdugo et al, 2020;Faucheu et al, 1995). The presence of .…”
Section: Evolutionary Symmetry Between the Mechanisms Of Casp-1-like mentioning
confidence: 84%